2017
DOI: 10.1007/s10549-017-4467-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle impact on breast cancer-specific and all-cause mortality

Abstract: Purpose While several studies have evaluated the association of combined lifestyle factors on breast cancer-specific mortality, few have included Hispanic women. We constructed a “healthy behavior index” (HBI) and evaluated its associations with mortality in non-Hispanic White (NHW) and Hispanic women diagnosed with breast cancer from the southwestern U.S. Methods Diet and lifestyle questionnaires were analyzed for 837 women diagnosed with invasive breast cancer (1999–2004) in New Mexico as part of the 4-Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 99 publications
(115 reference statements)
0
41
0
Order By: Relevance
“…In the E3N cohort, adherence of postmenopausal women to a healthy lifestyle by following the recommendations for smoking, BMI, alcohol consumption, fruit and vegetable consumption, and PA, prevented BC by 6.3% [24]. However, an increased risk of breast cancer-specific mortality was found for individuals with healthy behavior index compared to those with a lower healthy lifestyle score, however, the results was not statistically significant [14]. Therefore, it seems that adherence to healthy lifestyle could be used as a good preventive measure to reduce BC.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the E3N cohort, adherence of postmenopausal women to a healthy lifestyle by following the recommendations for smoking, BMI, alcohol consumption, fruit and vegetable consumption, and PA, prevented BC by 6.3% [24]. However, an increased risk of breast cancer-specific mortality was found for individuals with healthy behavior index compared to those with a lower healthy lifestyle score, however, the results was not statistically significant [14]. Therefore, it seems that adherence to healthy lifestyle could be used as a good preventive measure to reduce BC.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, Sanchez-Zamorano et al concluded that healthy lifestyle was associated with a decreased risk of having BC [13]. However, some other studies failed to find any association [14]. It must be kept in mind that these studies were conducted in western countries and to our knowledge, no study was done in eastern countries, specifically Iran, investigating the healthy lifestyle factors in relation to risk of BC.…”
Section: Introductionmentioning
confidence: 95%
“…All these previous cohort studies have estimated the contribution of a simultaneous adherence to healthy lifestyles in general population settings, with lack of further analysis among groups of individuals at different health risk, for which little evidence is available to date [6,13,14,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…2 Dietary components contribute to the etiology of 30-50% of all breast cancers. 3,4 However, it is important to consider that in order to permanently modify breast cancer risk, the dietary exposures may need to take place at times when the mammary tissue is undergoing extensive modeling. Mammary glands begin to develop during the prenatal life, but continue their remodeling during postnatal life, puberty, pregnancy and lactation, becoming more susceptible to carcinogenesis and making the influence of nutrition more important during those stages.…”
Section: Introductionmentioning
confidence: 99%